Investigation of Money Laundering Cases by Investigators Who Do Not Investigated the Predicate Crime - Syakur, Syahrijal (Corruptio, 2023)
Combining predicate crime investigations with money laundering cases is very possible if investigators find sufficient preliminary evidence of the occurrence of money laundering crimes when investigating predicate crimes. Then the merger of predicate crime investigations and money laundering cases is the authority given to investigators. This paper aims to find out about the investigation of money laundering case by other investigators who did not investigate the predicate crime, and who have not investigated the predicate crime. The research method used in this paper is a doctrinal method with a statutory, case, and conceptual approach. The results of this study are that if in accordance with Article 74 of the Money Laundering Law in conjunction with Article 2 paragraph (1) of the Money Laundering Law, the two investigative agencies have the same authority to investigate predicate crimes and both are also authorized to investigate money laundering cases, the investigator agency is authorized to investigate money laundering cases where the predicate crime investigation was carried out by investigators from different agencies.